Manajemen Positif Coping Ibu Hamil Melalui Senam Hamil - Yunikartika M. Sudin; Margareta A. Ndi; Ordilia Y. Viven; Nur Dafiq; Yosef Adrian Beo (Pusat Riset dan Inovasi Nasional, 2022)
A woman is said to be ready to get pregnant if she has gone through the process of achieving physical readiness, mental readiness, and economic readiness. Pregnant women are prone to experiencing psychological problems such as anxiety and depression which are closely related to the birthing process. Some pregnant women feel worried about the delivery process due to their previous experience of childbirth which was quite painful. This Community Service is carried out to help reduce maternal psychological problems during pregnancy by increasing positive individual coping through pregnancy exercise. This PKM is carried out using pregnant women's health interventions through counseling and pregnancy exercises. Pregnant women gain knowledge about stress management and know the techniques in pregnancy exercise. Through pregnancy exercise, it can reduce stress levels in pregnant women after covid 19.